Factors Driving Consumers' Purchase Intention Towards Electric Two- Wheelers - Basnet, Osica (Ganeshman Darpan, 2026)
In the Kathmandu Valley, Nepal, an area that suffers from extreme air pollution from traditional fuel-powered vehicles, this dissertation explores the factors influencing consumer purchase intentions toward electric two-wheelers, or e-bikes. The study’s main goal is to investigate how consumers’ decisions to purchase electric two-wheelers are influenced by social influence, perceived economic benefits, charging infrastructure, and environmental concerns. A systematic questionnaire was used to gather data from 379 respondents who were from the districts of Kathmandu, Lalitpur, and Bhaktapur. To investigate the connections between the important variables, the study used both descriptive and inferential statistical techniques, such as regression and correlation analysis. The findings reveal that environmental concern and perceived economic benefit are significant drivers of purchase intention, with respondents more likely to adopt e-bikes if they recognize their environmental and cost-saving advantages. Charging infrastructure, while important, remains a major barrier to adoption due to concerns about the availability and reliability of charging stations. Social influence plays a moderate role in shaping purchase intentions, with peer pressure and media exposure contributing to the decision-making process, though not as strongly as the environmental and economic factors. The study concludes that a combination of infrastructural improvements, public awareness campaigns, and financial incentives is necessary to boost e-bike adoption in Kathmandu Valley. Recommendations for policymakers and manufacturers include focusing on expanding charging infrastructure and making e-bikes more affordable to overcome the barriers identified in the research.